Method for producing fiber yarn

The method of producing fiber yarn by depolymerizing aromatic polyester with a manganese-based catalyst and subsequent repolymerization and melt-spinning addresses the issues of coloring and property degradation in recycled polyester fibers, resulting in yarns with superior physical properties.

JP2025063425APending Publication Date: 2025-04-16TEJIN FIBERS LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172604
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Regenerated aromatic polyester fibers produced through depolymerization and repolymerization often suffer from coloring issues and decreased molecular weight, crystallinity, and heat resistance due to residual additives and by-products.

Method used

A method for producing fiber yarn using bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester in the presence of a manganese-based catalyst, followed by repolymerization and melt-spinning to form fiber yarn.

Benefits of technology

The method achieves fiber yarns with excellent physical properties, comparable to those made from virgin polymers, while minimizing discoloration and maintaining high molecular weight, crystallinity, and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063425000001
    Figure 2025063425000001
  • Figure 2025063425000002
    Figure 2025063425000002
  • Figure 2025063425000003
    Figure 2025063425000003
Patent Text Reader

Abstract

To provide a fiber yarn less in coloration the same as fiber yarns composed of only a virgin polymer (polymer produced by polymerizing a monomer without undergoing depolymerization), in a producing method of fiber yarn using an aromatic dicarboxylic acid bis(hydroxyl alkyl) obtained by depolymerizing aromatic polyesters and excellent in physical properties.SOLUTION: A method for producing fiber strands using aromatic dicarboxylic acid bis(hydroxyalkyl) obtained by depolymerizing aromatic polyester, where the depolymerization is carried out in the presence of a manganese-based catalyst, with the amount of catalyst used being 20 to 500 mmol% relative to the aromatic polyester, and the aromatic dicarboxylic acid bis(hydroxyalkyl) obtained through depolymerization is re-polymerized to form a polyester polymer, which is then spun by melt spinning to create fibers.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a fiber yarn, and more particularly to a method for producing a fiber yarn using a bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester. [Background technology]

[0002] Aromatic polyesters, such as polyethylene terephthalate, are widely used as fibers, films, resins, etc., due to their excellent properties. However, in the manufacturing and processing steps, unused polyester raw materials and waste and offcuts in the form of fibers, films, and other shapes are inevitably generated. In addition, fibers, films, and resin molded products that are distributed and used as polyester products are discarded not only after use but also in an unused state. In recent years, various technologies have been developed to combat the environmental damage caused by such waste.

[0003] For example, as a method for reusing the above-mentioned process scraps, scraps, unused raw materials, and product waste, material recycling, chemical recycling, thermal recycling, etc. have been proposed. Among them, chemical recycling, particularly chemical recycling in which a monomer in the form of one molecule of aromatic dicarboxylic acid and two molecules of diol bonded by an ester group, or an intermediate obtained by depolymerizing this to an oligomer further having an ester bond, is used again, is an excellent method from the viewpoint of requiring less energy and of minimizing the deterioration of quality associated with recycling, since recycled aromatic polyester can be produced by a direct polycondensation reaction.

[0004] A more specific example of the above method is a method in which polyethylene terephthalate is depolymerized in ethylene glycol to obtain bis(2-hydroxyethyl) terephthalate, which is then polycondensed to obtain a recycled aromatic polyester. However, the recycled aromatic polyester obtained by this method has a problem of being easily discolored, and therefore attempts have been made to solve this problem.

[0005] For example, in Patent Document 1, as a step for removing coloring substances, an adsorption process in which the coloring substances are brought into contact with an adsorbent, a decomposition process in which the coloring substances are decomposed with a decomposing agent, a reduction process in which the coloring substances are reduced with a reducing agent, etc. are attempted. However, although coloring substances such as dyes that are clearly mixed into the polymer are removed to a certain extent, the quality of the polyester polymer with reduced coloring at the same level as that of normally produced polyester polymers is not obtained.

[0006] Furthermore, in fiber yarns and fiber products using recycled aromatic polyester obtained by repolymerization after depolymerization, in addition to the above-mentioned coloring problem, additives such as catalysts and by-products (diethylene glycol, etc.) that were added to the polyester before depolymerization tend to remain, resulting in problems such as a decrease in molecular weight (intrinsic viscosity), melting point or crystallinity, and poor heat resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-88096 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in consideration of the above background. An object of the present invention is to provide a fiber yarn having excellent physical properties and little coloring equivalent to a fiber yarn composed only of a virgin polymer (a polymer produced by polymerizing a monomer without going through depolymerization) in a method for producing a fiber yarn using a bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester. [Means for solving the problem]

[0009] The present invention is a method for producing a fiber yarn using a bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester, the method being characterized in that the depolymerization is carried out in the presence of a manganese-based catalyst, the amount of the catalyst being 20 to 500 mmol% based on the polyester, the bis(hydroxyalkyl) aromatic dicarboxylate obtained by the depolymerization is repolymerized to form a polyester polymer, and the polyester polymer is melt-spun into a fiber. Effect of the Invention

[0010] According to the present invention, in a method for producing a fiber yarn using a bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester, it is possible to provide a fiber yarn that is as little colored as a fiber yarn composed only of a virgin polymer (a polymer produced by polymerizing a monomer without going through depolymerization) and has excellent physical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below.

[0012] [Aromatic polyester] The aromatic polyester is a polymer that is composed of an aromatic dicarboxylic acid component and a diol component and has an ester bond in the main chain of the polymer.

[0013] Examples of dicarboxylic acid components include terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-tetrabutylphosphonium isophthalic acid, and 5-sodium sulfoisophthalic acid. Of these, terephthalic acid and 2,6-naphthalenedicarboxylic acid are preferred.

[0014] As the diol component, an aliphatic glycol having 2 to 20 carbon atoms can be used. Examples of the diol component include ethylene glycol, 1,3-propanediol, propylene glycol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, decamethylene glycol, cyclohexanedimethanol, cyclohexanediol, and dimer diol. Of these, ethylene glycol, 1,3-propanediol, and 1,4-butanediol are preferred.

[0015] As the diol component, a polyalcohol can be used in place of or in combination with the above-mentioned aliphatic glycol having 2 to 20 carbon atoms. In this case, a long-chain glycol having a molecular weight of 200 to 100,000 is used. Examples of the long-chain glycol include polyethylene glycol, poly-1,3-propanediol, poly-1,2-propanediol, and polytetramethylene glycol.

[0016] As the aromatic polyester, preferably polyalkylene terephthalate, particularly preferably polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate is used.

[0017] When the aromatic polyester is a polyalkylene terephthalate, it may contain other secondary polymer components as long as it is the main polymer component. In the present invention, an embodiment in which the aromatic polyester is mainly composed of a polyalkylene terephthalate is a preferred embodiment. Here, the main component means 60% by mass or more of the weight of the polymer.

[0018] When the aromatic polyester is a polyalkylene terephthalate, a polyester in which terephthalic acid is used as the dicarboxylic acid component and isophthalic acid or 5-sodium sulfoisophthalic acid is copolymerized as the copolymerization component is a preferred embodiment.

[0019] [Recycled polyester] As the aromatic polyester to be subjected to the depolymerization reaction, polyester recovered from a shaped product of aromatic polyester (referred to as "recovered polyester" in the present invention) can be used.

[0020] Examples of the shaped product include fibers, films, sheets, and other shapes. When the shaped product is a fiber, it may be in the form of a processed fiber product. When the shaped product is a film or sheet, it may be in the form of a tray or bag. Another example of the shape of the shaped product is a bottle.

[0021] The recycled polyester may be recovered from scraps or non-compliant products generated during the process of manufacturing shaped products. Examples of such scraps or non-compliant products include raw material pellets that do not meet the required standards, materials or cut pieces that are no longer needed during molding or processing, waste generated, transitional products or prototypes generated when changing brands, defective products, and cut pieces thereof.

[0022] As the recovered polyester, polyester fiber waste can also be used. In a preferred embodiment of the present invention, the polyester fiber waste accounts for preferably 50% by mass or more, more preferably 51% by mass or more, and even more preferably 70% by mass or more of the recovered polyester.

[0023] The polyester fiber waste includes waste materials collected during manufacturing, processing, or distribution before being released to the market as textile products or textile processed products, and textile products or textile processed products collected after being released to the market. The textile processed products may be used or unused. They may also be discarded.

[0024] The polyester fiber scraps may contain polyester fibers as the main component fiber, and may also contain natural fibers such as cotton, wool, and silk, chemical fibers derived from natural materials such as rayon, cupra, acetate, and lyocell, and synthetic fibers other than polyester fibers such as polyamide fibers, acrylic fibers, and urethane fibers. The main component fiber here means 60% or more by mass of the fiber weight.

[0025] The polyester fiber scraps may be colored, or may be cationic dyeable polyester fibers that can be dyed with cationic dyes having excellent color development and vividness. The cationic dyeable polyester fibers are copolymerized aromatic polyesters that contain, as a copolymerization component, an aromatic dicarboxylic acid component having a sulfonate group as a substituent on the aromatic ring, to which a cationic dye can be ionically bonded.

[0026] [Aromatic dicarboxylate bis(hydroxyalkyl)] The aromatic polyester described above is depolymerized in the presence of a catalyst to obtain a bis(hydroxyalkyl) aromatic dicarboxylate. The resulting bis(hydroxyalkyl) aromatic dicarboxylate will vary depending on the dicarboxylic acid component and the diol component of the aromatic polyester subjected to the depolymerization reaction.

[0027] When the dicarboxylic acid component is terephthalic acid, a bis(hydroxyalkyl) benzenedicarboxylate is obtained by the depolymerization reaction. This is sometimes called "BHAT" (bishydroxyalkyl terephthalate). This is a preferred embodiment of the present invention. That is, it is preferred that the bis(hydroxyalkyl) aromatic dicarboxylate is a bis(hydroxyalkyl) benzenedicarboxylate.

[0028] When the dicarboxylic acid component of the aromatic polyester is terephthalic acid and the alkylene glycol of the diol component is 1,3-propanediol (trimethylene glycol), bishydroxypropyl terephthalate (BHPT) is obtained by the depolymerization reaction.

[0029] When the dicarboxylic acid component of the aromatic polyester is terephthalic acid and the alkylene glycol of the diol component is 1,4-butanediol, bishydroxybutyl terephthalate (BHBT) is obtained by the depolymerization reaction.

[0030] When the dicarboxylic acid component of the aromatic polyester is terephthalic acid and the alkylene glycol of the diol component is ethylene glycol, the depolymerization reaction produces bishydroxyethyl terephthalate (BHET), which is also called bis(hydroxyethyl) benzenedicarboxylate.

[0031] [Depolymerization] In the present invention, a manganese catalyst is used as a depolymerization catalyst. Examples of the manganese catalyst include fatty acid salts, carbonates, sulfates, phosphates, oxides, hydroxides, halides, and alcoholates of manganese (Mn). Manganese oxide and manganese acetate are preferred, and manganese acetate is particularly preferred. These may be used alone or in combination of two or more.

[0032] Although the reason is unclear, the effect of the present invention is remarkable only when a manganese-based catalyst is used as a depolymerization catalyst. This effect is more remarkable when depolymerizing an aromatic polyester that does not contain a coloring substance than when depolymerizing an aromatic polyester that contains a coloring substance. For example, polyester polymers obtained by depolymerizing an aromatic polyester and then repolymerizing it often gradually become discolored due to long-term storage, but when the depolymerization reaction is performed using a manganese-based catalyst, this discoloration is clearly less.

[0033] The amount of the depolymerization catalyst used is 20 to 500 mmol%, preferably 30 to 300 mmol%, and particularly preferably 50 to 150 mmol%, based on the aromatic polyester to be subjected to the depolymerization reaction. Here, "mol%" indicates the ratio of the number of catalyst molecules to the repeating units of the aromatic polyester, and "mmol%" is 1000 times the number. If the amount of the catalyst used is less than 20 mmol%, the catalytic activity is insufficient, and if it exceeds 500 mmol%, the effect of suppressing discoloration is reduced.

[0034] When other catalysts are used as the depolymerization reaction catalyst, the depolymerization reaction does not proceed sufficiently with such a small amount of catalyst. However, by using a manganese-based catalyst, the depolymerization reaction can be carried out with such a small amount of catalyst.

[0035] The depolymerization catalyst is preferably used as a solution in which it is dissolved in alkylene glycol beforehand. As the alkylene glycol, it is preferable to use the same alkylene glycol as the diol component constituting the aromatic polyester to be subjected to the depolymerization reaction, or the same alkylene glycol as the diol component constituting the aromatic polyester to be obtained by later polymerizing the aromatic dicarboxylate bis(hydroxyalkyl) obtained by the depolymerization reaction, and it is particularly preferable to use the same alkylene glycol as the diol component constituting the aromatic polyester to be subjected to the depolymerization reaction. The alkylene glycol may be a mixture.

[0036] The alkylene glycol will be described in more detail below. When at least one of the aromatic polyester to be subjected to the depolymerization reaction and the polyester polymer to be obtained later by polymerization is polyethylene terephthalate, it is preferable to use ethylene glycol.

[0037] When at least one of the aromatic polyester to be subjected to the depolymerization reaction and the polyester polymer to be obtained later by polymerization is polytrimethylene terephthalate, it is preferable to use 1,3-propanediol (trimethylene glycol).

[0038] When at least one of the aromatic polyester to be subjected to the depolymerization reaction and the aromatic polyester to be obtained later by polymerization is polybutylene terephthalate, it is preferable to use 1,4-butanediol.

[0039] 〔purification〕 The aromatic dicarboxylate bis(hydroxyalkyl) obtained by depolymerization is preferably crystallized in alkylene glycol by lowering the temperature, preferably from 60° C. or higher to 25° C. or lower, more preferably to 15° C. or lower.

[0040] After the crystallization, it is preferable to separate the solid matter of the aromatic dicarboxylate bis(hydroxyalkyl) from its alkylene glycol solution into a solid-liquid separation. In this case, the alkylene glycol content in the cake, which is the solid matter after the solid-liquid separation, is preferably 100% by mass or less, more preferably 55% by mass or less, still more preferably 1 to 30% by mass, and particularly preferably 5 to 25% by mass, based on the weight of the aromatic dicarboxylate bis(hydroxyalkyl) in the cake.

[0041] The amount of alkylene glycol used in the depolymerization reaction is 2 to 20 times, and preferably 3 to 10 times, the amount of the aromatic polyester to be subjected to the depolymerization reaction, by weight. By using alkylene glycol in this range and carrying out crystallization and solid-liquid separation, the amount of the depolymerization catalyst and other foreign matter mixed into the aromatic dicarboxylate bis(hydroxyalkyl) can be reduced.

[0042] After solid-liquid separation, the cake of bis(hydroxyalkyl) aromatic dicarboxylate is preferably washed with water or alkylene glycol, preferably water, as a washing liquid. This washing is preferably carried out using a Nutsche filter while spraying the washing liquid. By carrying out these treatments, the remaining depolymerization catalyst and other substances that cause coloring can be washed away, and a more highly purified bis(hydroxyalkyl) aromatic dicarboxylate can be obtained.

[0043] The amount of the washing liquid is preferably 1 to 100 times, more preferably 1.5 to 10 times, the weight of the cake. The liquid temperature during washing is preferably 0 to 40° C. If the liquid temperature exceeds 40° C., the cake itself tends to dissolve, undesirably decreasing the yield.

[0044] Thereafter, the resulting mixture is dried in a vacuum dryer or the like to obtain a bis(hydroxyalkyl) aromatic dicarboxylate. When the alkylene glycol used for washing is the same as the diol component of the polyester polymer to be obtained by repolymerization, drying is not necessary.

[0045] [Repolymerization] The bis(hydroxyalkyl) aromatic dicarboxylate obtained by the depolymerization reaction is repolymerized to form a polyester polymer, which is an aromatic polyester having bis(hydroxyalkyl) aromatic dicarboxylate as a repeating unit.

[0046] The term "repolymerization" used herein is a term used to refer to the repolymerization of bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester, which was originally a polymer, in the present invention, and is synonymous with "polymerization."

[0047] As the catalyst used in the polycondensation reaction of the repolymerization, known catalysts such as antimony, germanium and titanium catalysts can be used, with antimony catalysts being preferred, and diantimony trioxide being particularly preferred.

[0048] This polycondensation reaction is preferably carried out while discharging the alkylene glycol generated in the polycondensation reaction outside the reactor. The amount of the catalyst used is preferably 10 to 1000 ppm based on the weight of the aromatic dicarboxylate bis(hydroxyalkyl) to be subjected to the polycondensation reaction of repolymerization.

[0049] After the polycondensation reaction, it is preferable to add a phosphorus-based stabilizer. The amount of the phosphorus-based stabilizer is preferably 1 to 100 ppm based on the weight of the aromatic dicarboxylate bis(hydroxyalkyl) used in the polycondensation reaction.

[0050] The obtained polyester polymer is a polyester polymer that is less prone to discoloration such as yellowing, which is a different property from the case where a depolymerization catalyst such as magnesium hydroxide, sodium hydroxide, potassium hydroxide, magnesium carbonate, sodium carbonate, or potassium carbonate, which has been conventionally used as a depolymerization catalyst for obtaining bis(hydroxyalkyl) aromatic dicarboxylate, is used.

[0051] The color difference was visible even at the stage of the aromatic dicarboxylate bis(hydroxyalkyl) obtained during the process, but the color difference after repolymerization into a polyester polymer was * , a * and b * Among the values, especially b * The polyester polymer produced under the conditions of the present invention using a manganese-based depolymerization catalyst has a b value of -3 or less, preferably -3.5 or less. * The value can be obtained. In contrast, when other depolymerization catalysts were used, the resulting polyester polymer was highly colored and in some cases * takes a positive value, resulting in a strong yellowish color.

[0052] The reason why the present invention can obtain a polyester polymer with little coloration is unclear, but it is believed that the reason is that the use of a manganese catalyst allows depolymerization at a low catalyst concentration in the depolymerization reaction, making it difficult to produce colored by-products. Another reason is that the manganese catalyst is easily dissociated from the aromatic dicarboxylate bis(hydroxyalkyl) during crystallization, making it difficult to remain as an impurity.

[0053] [Alkali metals and alkaline earth metals] In the polycondensation reaction of the repolymerization, it is preferable to carry out the polycondensation reaction of the aromatic dicarboxylate bis(hydroxyalkyl) in the presence of an alkali metal and / or an alkaline earth metal, which can suppress fluctuations or deterioration of heat resistance and other physical properties.

[0054] Examples of alkali metals include lithium, sodium, potassium, rubidium, and cesium, and preferably sodium and potassium are used. Examples of alkaline earth metals include calcium, barium, beryllium, and magnesium, and preferably calcium and magnesium are used. Particularly preferred as the alkali metal and / or alkaline earth metal is sodium.

[0055] The amount of alkali metal and / or alkaline earth metal used is preferably 5 to 1000 ppm, more preferably 10 to 500 ppm, based on the mass of the aromatic bis(hydroxyalkyl) dicarboxylate, from the viewpoint of the hue of the polyester polymer after repolymerization.

[0056] The alkali metal and / or alkaline earth metal are preferably used in the form of their respective salts. That is, they are preferably used as alkali metal salts and / or alkaline earth metal salts. Examples of components constituting the alkali metal salts and / or alkaline earth metal salts include propionic acid, acetic acid, oxalic acid, formic acid, and carbonic acid, and preferably acetic acid is used.

[0057] As the alkali metal salt and / or alkaline earth metal salt, preferably lithium acetate, sodium acetate, potassium acetate, calcium acetate, barium acetate, magnesium acetate, and more preferably sodium acetate is used.

[0058] The reason why the addition of alkali metals and alkaline earth metals can suppress the fluctuation and deterioration of heat resistance and other physical properties is that when the aromatic polyester to be subjected to the depolymerization reaction contains recovered polyester, it often contains copolymerized aromatic polyesters that contain isophthalic acid components modified with sulfonate groups, which have good dyeability with cationic dyes, as a copolymerization component in order to improve the dyeability of fibers and textile products. Particularly common is copolymerized polyethylene terephthalate in which isophthalic acid components with alkali (earth) metal sulfonate groups, especially 5-sodium sulfoisophthalic acid, are copolymerized.

[0059] In this case, a small amount of an aromatic dicarboxylate bis(hydroxyalkyl) containing an alkaline (earth) metal sulfonate group (e.g., bis(2-hydroxyethyl) 5-sodiosulfoisophthalate) is formed by the above-mentioned depolymerization reaction, which dissolves in the alkylene glycol. The aromatic dicarboxylate bis(hydroxyalkyl) (e.g., BHET) obtained by solid-liquid separation exhibits high acidity, and the polyester polymer (e.g., polyethylene terephthalate) obtained by repolymerizing this exhibits a significant decrease in crystallinity and molecular weight. This causes a problem of reduced heat resistance. This problem can be solved by carrying out the polycondensation reaction of the repolymerization in the presence of a polymerization catalyst and an alkali metal and / or an alkaline earth metal.

[0060] By neutralizing the high acidity of the bis(hydroxyalkyl) aromatic dicarboxylate after solid-liquid separation with an alkaline metal or metal compound, the crystallinity and molecular weight of the polyester polymer obtained by repolymerization can be made comparable to that of virgin polyester.In some cases, this can further increase the freedom to change reaction conditions such as the temperature and pressure of the polycondensation reaction in the repolymerization, making it easier to control the crystallinity, melting point, and molecular weight.

[0061] When a recovered polyester is used as the aromatic polyester to be subjected to the depolymerization reaction, the variation range of the physical properties of the resulting polyester polymer can be suppressed to a small range by carrying out the polycondensation reaction of repolymerization in the presence of an alkali metal and / or an alkaline earth metal, regardless of the presence or absence of a copolymer component having a sulfonate group in the recovered polyester.

[0062] In addition, since the alkali metal and / or alkaline earth metal is added during the polycondensation reaction of repolymerization, the alkali metal and / or alkaline earth metal will remain in the fiber thread form of the obtained polyester polymer.

[0063] [Polyester polymer] The polyester polymer obtained by the above-mentioned repolymerization has an intrinsic viscosity of preferably 0.3 to 2.0 dL / g, more preferably 0.4 to 1.5 dL / g, and particularly preferably 0.5 to 1.3 dL / g. If the intrinsic viscosity is less than 0.3 dL / g, the melt viscosity is low, spinnability is poor, and spinning breakage is likely to occur, which is undesirable, while if it exceeds 2.0 dL / g, the melt moldability is undesirable.

[0064] The polyester polymer obtained by the above-mentioned repolymerization has a terminal carboxyl group of preferably 20 equivalents / ton or less, more preferably 1 to 15 equivalents / ton, and particularly preferably 2 to 11 equivalents / ton. This is a lower terminal carboxyl group than that of commonly known virgin polyesters, and as a result, the resulting aromatic polyester is less prone to hydrolysis or thermal decomposition and has excellent deterioration resistance.

[0065] For this reason, the fiber thread obtained by the present invention is suitable for polyester fiber products (medical clothing) resistant to autoclave sterilization, polyester fiber for tire cords, and polyester monofilaments for paper machine nets, because polyester polymers with fewer terminal carboxyl groups are particularly suitable for these applications. Although the mechanism by which the number of terminal carboxyl groups decreases is not yet clear, the present inventors have confirmed that a clear significant difference exists.

[0066] [Fiber yarn] In the method for producing a fibrous thread of the present invention, the polyester polymer obtained by the above-mentioned repolymerization is melt-spun to form a fiber, thereby obtaining a fibrous thread. The melt spinning can be performed by a conventionally known melt spinning method.

[0067] The fiber thread may be a fiber thread consisting of only the polyester polymer obtained by the repolymerization described above, a fiber thread made by blending (mixing) the polyester polymer obtained by repolymerization with a virgin polyester, a composite fiber fiber having the polyester polymer obtained by repolymerization as one component and a different type of virgin polyester as the other component, a composite fiber fiber having the polyester polymer obtained by repolymerization as one component and a polyester polymer obtained by repolymerizing a different type of monomer component having a different monomer component as the other component, or a composite fiber fiber of the polyester polymer obtained by repolymerization and a different type of polymer other than polyester.

[0068] Examples of fiber thread forms include long fibers (filaments) primarily used for processed yarns such as POY-DTY and blended yarns, and woven and knitted fabrics; short fibers (staple fibers) primarily used for spun yarns, nonwoven fabrics, fiber structures such as padding and wadding for bedding and clothing, and cushions; industrial fibers (industrial yarns) primarily used for fibers reinforcing rubber and resin for tires and belts, fishing nets, tent fabrics, canvas, etc.; and monofilaments primarily used for screen gauze, screen doors, brushes, civil engineering nets, papermaking machine nets, racket strings, etc.

[0069] In melt spinning, the polyester polymer is melted and extruded from a spinneret, and then cooled by blowing air from a direction perpendicular to the yarn to cause a difference in molecular orientation in the fiber cross section. The yarn is then stretched, and then subjected to a relaxation heat treatment to cause three-dimensional crimping, thereby imparting three-dimensional crimping.

[0070] In this case, it is possible to obtain a fiber filament having the same crimping performance as that of virgin polyester polymer, which has good cushioning properties and is suitable for use as a main fiber in wadding or fiber structures. The cross-sectional shape of the filamentous fiber may be any shape selected according to purpose, such as circular, irregular, solid or hollow.

[0071] [Textile products] Examples of textile products containing fiber threads include clothing, linings, interlinings, socks, belly warmers, hats, gloves, clothing wadding, nightwear, futon coverings, futon covers, bedding wadding, artificial leather, synthetic leather, carpets, tent fabrics, hose fabrics, canvas, vehicle seat covering materials, vehicle seat cushioning materials, sanitary materials, wiping materials, polishing pads, polishing cloths, medical clothing, food filters, wallpaper, filter substrates, tires, seat belts, airbag base fabrics, brushes, screen doors, fishing nets, industrial machine nets, reinforcing nets, and civil engineering nets. EXAMPLES

[0072] The effects of the present invention will be specifically described below by giving examples using examples. Note that each value in the examples was determined by the following measurement methods. In addition, in the description of the amount of catalyst added, the "mol %" of the catalyst relative to the polyester indicates the ratio of the number of catalyst molecules to the constituent units of the polyester.

[0073] (1)Measurement method 1) Polymer color The polymer (5 g) was pressed between two metal plates to form a plate, which was then heated at 140° C. for 2 hours to crystallize the sample. The measurement sample was measured for hue L according to JIS Z8781-4:2013 using a measuring device ("ZE-6000" manufactured by Nippon Denshoku Industries Co., Ltd.). * , b * The difference is the index of yellowness (L * -b * ) value. (L * -b * ) The higher the value, the less yellowish the color.

[0074] 2) Elemental content The amount of each element in the polymer was measured by heating and melting the polymer to create a circular disk, and then measuring the amount of metal corresponding to the catalyst used using a fluorescent X-ray analyzer "ZSXPrimus II" manufactured by Rigaku Corporation. In the table, "ND" means below the detection limit (5 ppm or less).

[0075] 3) Intrinsic viscosity number (IV) 0.6 g of polyester was dissolved in 50 cc of o-chlorophenol by heating, then cooled, and the solution viscosity was measured at 35°C using an Ubbelohde viscometer. The viscosity was calculated using a separately prepared calibration curve.

[0076] 4) Glass transition point (Tg), melting point (Tm), crystallization temperature (Tc) A 10 mg sample was cut out and placed in an aluminum pan, and the melting point was measured using a DSC Q10 manufactured by TA Instruments-Waters LLC. The measurement conditions were as follows: first, the sample was heated from 25°C to 300°C at a rate of 20°C / min, and then quenched by rapid cooling. The quenched sample was then heated from 25°C to 300°C at a rate of 20°C / min, and the crystalline melting point was determined.

[0077] 5) Diethylene glycol (DEG) content The polyester was decomposed using hydrazine hydrate, and the content of diethylene glycol in the decomposition product was measured using a gas chromatograph (HP6850 manufactured by Hewlett-Packard Co.).

[0078] 6) Quantitative determination of carboxyl end group (COOH) concentration According to a conventional method, 0.1 g of a polyester sample is dissolved in benzyl alcohol and titrated with a 0.02 mol / liter NaOH aqueous solution, and the carboxyl end group concentration is calculated according to the following formula. COOH (equivalents / ton) = ((AB) x 0.02 x f x 10 6 ) / (0.1×10 3 ) Here, A is the alkali consumption (ml), B is the blank (alkali consumption measured without adding a polyester sample) (ml), and f is a constant.

[0079] 7) Fiber fineness Measurements were performed in accordance with JIS L1013:2010 8.3.1 Method A.

[0080] 8) Number of filaments in the fiber Measurements were performed in accordance with JIS L1013:2010 8.4.

[0081] 9) Fiber strength Measurements were performed in accordance with JIS L1013:2010 8.5.1.

[0082] 10) Fiber color The polyester fiber was knitted into a 30 cm long tube using a 12 gauge circular knitting machine, and the hue L * , b * The difference is the index of yellowness (L * -b * ) value. (L * -b * ) The higher the value, the less yellowish the color.

[0083] 11) Strength retention rate After autoclave treatment described below, the average fiber strength value taken from the fabric sample was divided by the fiber strength before autoclave treatment to obtain a percentage.

[0084] 12) Tear strength of fabric Measurements were taken in accordance with JIS L1096:2010 8.17.4 D method (pendulum method) and the average value in the warp and weft directions was calculated.

[0085] (2) Aromatic polyester Hereinafter, polyethylene terephthalate is abbreviated as "PET". As an aromatic polyester to be subjected to depolymerization, a commercially available PET was prepared. In addition, as another aromatic polyester to be subjected to depolymerization, a pellet-shaped cationic dyeable PET (5-sodium sulfoisophthalic acid copolymerized PET) was prepared. This cationic dyeable PET was produced according to the following Reference Example 1. The physical properties, sulfur atom (S) and sodium (Na) content, and color tone of these aromatic polyesters are shown in Table 1.

[0086] [Reference Example 1] Production of cationic dyeable PET (5-sodium sulfoisophthalic acid copolymerized polyethylene terephthalate) In a reaction vessel under normal pressure and under a nitrogen atmosphere, 191.3 parts by mass of dimethyl terephthalate (DMT), 124.2 parts by mass of ethylene glycol (EG), and 4.4 parts by mass of sodium dimethyl 5-sulfoisophthalate (manufactured by Takemoto Oil Co., Ltd.) were added, and 0.07 parts by mass of manganese acetate and 0.22 parts by mass of sodium acetate were added as transesterification reaction catalysts. The reaction temperature was set to 240°C, and the transesterification reaction was carried out while removing methanol.

[0087] Next, 0.07 parts by mass of diantimony trioxide and 0.03 parts by mass of orthophosphoric acid were added to the reactant after the ester exchange reaction was completed. The temperature inside the reaction vessel was kept at 285°C, and the pressure was gradually reduced at normal pressure for 10 minutes, at 4 kPa for 10 minutes, and at 0.4 kPa for 40 minutes, respectively, and a polycondensation reaction was carried out while distilling off ethylene glycol and the like generated during the reaction outside the reaction vessel, to obtain 5-sodium sulfoisophthalic acid-copolymerized polyethylene terephthalate.

[0088] [Table 1]

[0089] Example 1 300 parts by mass of commercially available PET, 1500 parts by mass of ethylene glycol (hereinafter referred to as "EG"), and 0.38 parts by mass of manganese acetate (100 mmol% relative to PET) as a depolymerization catalyst were placed in a 2L separable flask and nitrogen gas was sealed in. The manganese acetate was dissolved in EG beforehand and then placed in the flask. The PET used was not colored, and contained 297 ppm of antimony (Sb) in terms of Sb atoms as a polymerization catalyst used in the production of PET.

[0090] Thereafter, the nitrogen gas-filled separable flask was heated with a mantle heater to an internal temperature of 220°C, and the PET depolymerization reaction was carried out for 4 hours at normal pressure with stirring, to obtain an EG solution of bis(hydroxyethyl)benzenedicarboxylate (hereinafter referred to as "BHET"). This solution was colorless and transparent, with no visible coloration.

[0091] After the depolymerization, the EG solution of BHET was filtered through a 200 μm mesh to remove solids, and then slowly cooled to 70°C. With stirring and cooling, the temperature was lowered from 70°C to 40°C over 10 minutes (elapsed time 0→10 minutes), then from 40°C to 30°C over 50 minutes (elapsed time 10→60 minutes), and then from 30°C to 15°C over 120 minutes (elapsed time 60→180 minutes). Thereafter, the mixture was stirred for 60 minutes while maintaining the internal temperature at 15° C., and then the internal temperature was lowered to allow BHET crystals to precipitate (total of 4 hours), thereby obtaining a BHET / EG slurry.

[0092] This BHET / EG slurry was pressed using a filter press manufactured by Nippon Filter Equipment Co., Ltd., and solid-liquid separation was performed into a solid BHET cake and liquid EG. The separated solid BHET cake contained 35 mass% of EG based on the weight of the BHET cake. The EG-separated BHET cake was washed with water using a Nutsche filter while spraying it with 25°C pure water in an amount twice its weight, to obtain BHET after washing with water.

[0093] After washing with water, the BHET was dried in a vacuum dryer at 50° C. for 8 hours to obtain dried BHET. The obtained dried BHET was white and was free of any foreign matter.

[0094] Next, the dried BHET is used to repolymerize the PET. 254 parts by mass of this dried BHET was charged into a reaction vessel at normal pressure under a nitrogen atmosphere together with 0.007 parts by mass of a phosphorus-based stabilizer and 0.07 parts by mass of diantimony trioxide as a repolymerization catalyst. First, the temperature in the reactor was set to 285°C and the reaction was carried out at normal pressure for 10 minutes, then at a pressure of 4 kPa for 10 minutes, and then at a pressure of 0.4 kPa for 40 minutes. The pressure was gradually reduced, and the polycondensation reaction was carried out while distilling off the EG generated in the reaction outside the reactor. After that, the reaction product in the system was continuously extruded in a strand shape from the discharge part, cooled, and cut to obtain repolymerized PET in the form of granular pellets with a particle diameter of about 3 mm. The quality of the product is shown in Table 2.

[0095] This repolymerized PET was dried at 150°C for 5 hours, and then melted in a melt spinning system equipped with a screw extruder. It was introduced into a spin block at 285°C and discharged from a spinneret having 72 concentrically arranged discharge holes with a diameter of 0.23 mm at a flow rate of 36 g / min. The PET polymer flow was cooled and solidified by an air flow blown out of a cross-flow type blower, while being collected while being oiled by an oiling roller installed 200 cm below the spinneret, and taken up at a speed of 1250 m / min. 10 kg of the resultant undrawn yarn having a thickness of 317 dtex / 72 filaments was wound into a cheese shape. The undrawn yarn was then drawn by a standard method to obtain a multifilament having a fiber size of 83 dtex / 72 fil (1.2 dtex / fil), an intrinsic viscosity of 0.61 dL / g, a DEG of 0.7 mass%, a carboxyl end group concentration of 6.9 equivalents / ton, and a yarn strength of 4.8 cN / dtex. * -b * was 95.6.

[0096] This drawn yarn was used for the warp and weft, and woven into a 2 / 1 twill, scoured and relaxed with voile, then set using a pin tenter at 190°C dry heat, then dyed at 130°C under high pressure, dried, and then final set using a pin tenter at 190°C dry heat to produce a product. This product was autoclaved 200 times (relative humidity 100%, temperature 121°C, treatment time 30 minutes), and then yarns were removed from the product fabric to measure the yarn strength, which was 2.5 cN / dtex for the warp and 2.4 cN / dtex for the weft, with a strength retention of 51%.

[0097] The tear strength of the product was 30.4N in the warp direction, 28.4N in the weft direction, and 29.4N in average, which was sufficient for wearing. The product also had a soft feel and was comfortable to wear. The evaluation of the fiber is shown in Table 3.

[0098] [Table 2]

[0099] [Table 3]

[0100] Example 2 300 parts by mass of the 5-sodium sulfoisophthalic acid copolymerized PET obtained in Reference Example 1, 1500 parts by mass of EG, and 0.38 parts by mass of manganese acetate (100 mmol% based on the total dicarboxylic acid components of the 5-sodium sulfoisophthalic acid copolymerized PET) were placed in a 2 L separable flask and nitrogen was sealed in. At this time, the manganese acetate was dissolved in EG beforehand and then added.

[0101] Thereafter, the depolymerization reaction was carried out at 202°C for 4 hours while stirring under nitrogen gas atmosphere, to obtain a solution of BHET in EG after depolymerization. The obtained EG solution of BHET after depolymerization was gradually cooled to 70° C., and then the internal temperature was lowered while stirring and cooling in a thermostatic bath at 15° C. to precipitate crystals of BHET, thereby obtaining a BHET / EG slurry.

[0102] The BHET / EG slurry was pressed using a filter press manufactured by Nippon Filter Equipment Co., Ltd., and solid-liquid separation was performed into solid BHET and liquid EG to obtain a BHET cake, which contained 34% by mass of EG.

[0103] The BHET cake was washed with water using a Nutsche filter while spraying it with pure water in an amount twice its mass. The washed BHET cake was dried in a vacuum dryer at 50°C for 8 hours to obtain dried BHET.

[0104] In a reaction vessel under normal pressure and in a nitrogen atmosphere, 254 parts by mass of this dry BHET, 0.07 part by mass of diantimony trioxide, 0.005 part by mass of orthophosphoric acid, and 0.22 part by mass of sodium acetate were charged.

[0105] Next, the temperature inside the reaction vessel was set to 285°C, and the pressure was gradually reduced under the following conditions: normal pressure for 10 minutes, 4kPa for 10 minutes, and 0.4kPa for 40 minutes, and the polycondensation reaction was carried out while distilling off the EG generated during the reaction outside the reaction vessel. The reaction product in the system was then continuously extruded in a strand shape from the discharge port, cooled, and cut to obtain repolymerized PET in the form of granular pellets of about 3 mm. The quality of the final repolymerized PET is shown in Table 2.

[0106] The PET pellets were melt spun and drawn in the same manner as in Example 1 to obtain a multifilament fiber having a density of 83 dtex / 72 fil (1.2 dtex / fil), an intrinsic viscosity of 0.61 dL / g, DEG of 0.9 mass%, a carboxyl end group concentration of 10.1 equivalents / ton, and a yarn strength of 4.7 cN / dtex. The color of the fiber was L * -b * was 94.5.

[0107] This fiber was used for the warp and weft, and woven into a 2 / 1 twill. After scouring and relaxing with a voile, it was set using a pin tenter at 190°C dry heat, then high-pressure dyeing at 130°C was performed, and then it was dried and then final set was performed using a pin tenter at 190°C dry heat to produce a product. This product was autoclaved 200 times (100% relative humidity, 121°C, treatment time 30 minutes), and then the yarn was taken out from the product fabric and the yarn strength was measured. The warp was 2.3cN / dtex, the weft was 2.1cN / dtex, and the strength retention rate was 47%. The tear strength of the product was 29.2N for the warp and 28.0N for the weft, with an average of 28.6N, which was sufficient for wearing. The product also had a soft texture and a good wearing feel. The fiber evaluation is shown in Table 3.

[0108] Comparative Example 1 Instead of using manganese acetate as a depolymerization catalyst as used in Example 1, titanium tetraoxide was used. Since this titanium tetraoxide acts as a polymerization catalyst, 0.07 g of antimony trioxide was not added as a repolymerization catalyst when repolymerizing PET polymer from dried BHET. Other than this, the same procedure as in Example 1 was carried out, PET was depolymerized to obtain BHET, which was then repolymerized to obtain PET. The EG solution of BHET obtained after depolymerization was significantly colored, and the final PET was strongly yellowish in color. The quality is shown in Table 2.

[0109] The PET pellets were melt spun and drawn in the same manner as in Example 1 to obtain a multifilament fiber having a fiber density of 83 dtex / 72 fil (1.2 dtex / fil), an intrinsic viscosity of 0.61 dL / g, DEG of 2.3 mass%, a carboxyl end group concentration of 23.5 equivalents / ton, and a yarn strength of 4.8 cN / dtex. * -b * was 75.6.

[0110] This drawn yarn was used as the warp and weft, and woven in the same manner as in Example 1, followed by scouring, relaxing, setting, dyeing, drying and final setting to produce a finished product. This product was treated in an autoclave 200 times in the same manner as in Example 1, after which the yarns were removed from the product and the yarn strength was measured, revealing that the warp was 1.7 cN / dtex and the weft was 1.5 cN / dtex, with a strength retention rate of 33%. The tear strength of the product was 8.1 N for the warp and 7.1 N for the weft, for an average of 7.6, and it was prone to tearing and not suitable for practical use.

[0111] Comparative Example 2 Manganese acetate, which was used as a depolymerization catalyst in Example 1, was not used, and instead sodium hydroxide was used as a depolymerization catalyst. The rest of the experiment was carried out in the same manner as in Example 1. The depolymerization reaction did not proceed sufficiently, and a large amount of undecomposed PET remained in the flask. The amount of BHET was small, and repolymerization was not possible.

[0112] Comparative Example 3 Manganese acetate, which was used as a depolymerization catalyst in Example 1, was not used, and instead potassium carbonate was used as the depolymerization catalyst. The rest of the experiment was carried out in the same manner as in Example 1. Depolymerization did not proceed sufficiently, and a large amount of undecomposed PET remained in the flask. The amount of BHET was small, and repolymerization was not possible.

[0113] Comparative Example 4 The same procedure was carried out as in Example 1, except that manganese acetate used as a depolymerization catalyst was not used, and instead the same potassium carbonate as in Comparative Example 3 was used as the depolymerization catalyst, and the amount of potassium carbonate added was 9.0 parts by mass instead of 0.38 parts by mass in Example 1. Pellets of BHET and repolymerized PET obtained by repolymerizing the BHET were obtained. The repolymerized PET had a yellowish hue compared to Example 1 and commercially available PET. The quality is shown in Table 2.

[0114] Using the pellets of this repolymerized PET, melt spinning and drawing were carried out in the same manner as in Example 1 to obtain a multifilament fiber having 83 dtex / 72 fil (1.2 dtex / fil), an intrinsic viscosity of 0.61 dL / g, DEG of 0.7 mass%, a carboxyl end group concentration of 32.5 equivalents / ton, and a yarn strength of 4.7 cN / dtex. The color of the fiber was L. * -b * was 86.1.

[0115] This fiber was used as the warp and weft and woven in the same manner as in Example 1, and further refined, relaxed, set, dyed, dried and final set to produce a finished product. This product was treated in an autoclave 200 times in the same manner as in Example 1, and then the yarn was removed from the product and the yarn strength was measured, giving warp yarn of 1.6 cN / dtex, weft yarn of 1.3 cN / dtex, and strength retention of 31%, while the tear strength of the product was warp 8.0 N, weft 7.2 N, and average 7.6 N, which meant that it was prone to tearing and was not suitable for practical use.

[0116] Comparative Example 5 Depolymerization and repolymerization were carried out in the same manner as in Example 2, except that sodium acetate was not added. The repolymerized PET obtained by repolymerization was in an amorphous state without crystallization, and since the glass transition temperature was as low as 35°C, it was difficult to solidify by cooling and could not be made into pellets, and therefore could not be molded into fibers.

[0117] Comparative Example 6 Comparative Example 6 is an example in which depolymerization was not performed. Using commercially available PET pellets, melt spinning and drawing were carried out in the same manner as in Example 1 to obtain a multifilament fiber having 83 dtex / 72 filaments (1.2 dtex / fil), an intrinsic viscosity of 0.61 dL / g, DEG of 1.2 mass%, a carboxyl end group concentration of 31.5 equivalents / ton, and a yarn strength of 4.9 cN / dtex. The color of the fiber was L * -b * was 94.7.

[0118] This fiber was used as the warp and weft and woven in the same manner as in Example 1, and further refined, relaxed, set, dyed, dried and final set to produce a finished product. This product was treated in an autoclave 200 times in the same manner as in Example 1, and then the yarn was removed from the product and the yarn strength was measured, giving warp yarn of 1.5 cN / dtex, weft yarn of 1.3 cN / dtex, strength retention of 29%, and product tear strength of 7.8 N for warp and 6.9 N for weft, averaging 7.4 N, which meant that the product was prone to tearing and not suitable for practical use.

Claims

1. A method for producing a fiber yarn using a bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerizing an aromatic polyester, the method comprising the steps of: depolymerizing the aromatic polyester in the presence of a manganese catalyst in an amount of 20 to 500 mmol% based on the aromatic polyester; repolymerizing the bis(hydroxyalkyl) aromatic dicarboxylate obtained by depolymerization into a polyester polymer; and melt-spinning the polyester polymer into a fiber.

2. 2. The method for producing a fiber yarn according to claim 1, wherein the aromatic polyester is composed mainly of polyalkylene terephthalate.

3. 2. The method for producing fiber yarn according to claim 1, wherein the manganese-based catalyst is manganese acetate.

4. 2. The method for producing a fiber yarn according to claim 1, wherein the bis(hydroxyalkyl) aromatic dicarboxylate is a bis(hydroxyalkyl) benzenedicarboxylate.

5. 2. The method for producing a fiber yarn according to claim 1, wherein the repolymerization is carried out in the presence of a metal catalyst such as an alkali metal and / or an alkaline earth metal.

6. The method for producing a fiber yarn according to claim 1, wherein the aromatic polyester is a recycled polyester.

7. 2. The method for producing a fiber yarn according to claim 1, wherein the amount of terminal carboxyl groups in the polyester polymer is 20 equivalents / ton or less.

8. A textile product comprising the fiber yarn according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for producing bis-(2-hydroxyethyl) terephthalate and method for producing polyethylene terephthalate

    JP2008088096A